Industrial Symbiosis in climate change mitigation: role of effective facilitation in the Gauteng City Region - Ndovela, Mfundo Ndumiso (My University, 2022)
Under the Gauteng Industrial Symbiosis Programme (GISP) of the National Clean Production Centre of South Africa (NCPC-SA), facilitators assist industries in diverting waste from landfill sites through reuse as input in other industries. The programme aimed at diverting 300 000 tonnes of waste through an initial annual target of 40 synergies (relationships between two or more companies where they reuse waste). Facilitation primarily entails series of workshop engagements for synergy-identification and follow up sessions to ensure implementation. As elaborated in this study, when such waste resources are reused, Greenhouse Gas (GHG) emission is mitigated because use of virgin materials is reduced and waste transportation to landfill sites is avoided. The study therefore applied a qualitative study approach to assess GISP’s facilitation process and its impact on mitigation of climate change. Semi-structured interviews were conducted with officials from NCPC-SA and the Gauteng Province Department of Agriculture and Rural Development (GDARD). The study also collected secondary data from various GISP reports as well as related academic articles to analyse facilitation issues and challenges. The study finds that GISP facilitators play an important role in recruiting companies to attend the Business Opportunity Workshops (BOWs) where reusable waste resources are identified and recorded. Waste exchange partnerships are facilitated by GISP facilitators and follow up engagements are conducted in order to ensure that synergy partnerships are pursued so that the exchange of waste resources is achieved. The study also finds that through the GISP facilitation process approximately 111 000 tonnes of waste were diverted between 2014 to 2018, which contributed to mitigation of 139 351,62 tonnes of GHG emissions. Despite GISP’s success, the study identified several critical challenges related to facilitation which in turn undermined optimal contribution to climate change mitigation. As a result, GISP failed to meet its annual target of landfill waste diversion (300 000 tons of waste) mainly due to inadequate financial resources for companies to pursue synergies as well as limited number of GISP facilitators to conduct follow up engagements. In order to strengthen its facilitation, GISP launched an online synergy platform to allow companies to share data on waste resources they generate or waste resources they require. This facilitates faster matching of companies as well as better alignment in waste resource exchange. The GISP facilitators can then conduct follow up engagements to record the impacts in terms of tonnes of waste diverted and GHG emissions mitigated.
A research report submitted in partial fulfilment of the requirements of the degree of Masters of Urban Studies to the Faculty of Engineering and Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2022